Action research and possibilities of critical interculturality and decolonization of academic practice: Kanhgág (Kaingang) community Por Fi Ga /RS/ Brasil (PerCursos, 2021)
This paper brings experience reports on the possibilities of academic decoloniality arising from university research, if, under critical intercultural perspectives, they question current structures. Academic decoloniality is understood as processes in which the University and its instances can assist and legitimize autonomous community actions and formations, diverging from the usual way in which indigenous issues are established within Universities, generally without the participation of communities, as objects of study or sporadic participants in unpaid events. Based on the Action Research method, we selected a community demand for resolution through the research that resulted in a Social Sciences Dissertation. As a result of this study, it is stated that, since the enactment of laws that compel institutions to teach in their academic programs content that reflect indigenous versions of the country's history (Law 11.645 / 08), there has been a growth in visibility of these agents and their contents. However, these are still theoretical actions or isolated practices, of teachers and students, without the broad participation of the local community, thus configuring a functional interculturality, convenient to the State, which only “fits” the agents and themes in an uneven structure already in place. It is believed that the academy's decolonial potentials reside in the relationship of respect and reciprocity between its employees, research and the location, in this case, the Kanhgág Por Fi Ga community itself. It is necessary for the academy to be open to learning other epistemologies, building spaces that really work from the community, valuing knowledge from the residents.
Keywords: Action research; Interculturalities; Decoloniality; Kanhgág; Kaingang